1991
DOI: 10.1139/f91-184
|View full text |Cite
|
Sign up to set email alerts
|

Status and Trends of the Lake Ontario Macrobenthos

Abstract: Nalepa, T. F. 1991. Status and trends of the take Ontario macrsbenthos. Can. I. Fish. Aqe~at. Sei. 48: 1558- 1567.The benthic macroinvertebrate community sf Lake Ontario was examined relative to communities found in the other Great Lakes and also relative to trends over time. In the nearshore, populations are heavily influenced by municipal and industrial inputs. For example, oligochaete abundances in the nearshore are higher than in any of the other Great Lakes (excluding shallow Lake Erie), communities have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
12
2
Order By: Relevance
“…Furthermore, changes recorded in oUgochaete communities between 1982 and 1991 were the same as those attributed to a decrease of organic sedimentation (Lang, 1989b). However, the scardty of Peloscolex velutinus and Bythonomus lemani at a depth of 150 m (Lang, 1991), could indicate toxic effects in Lake Geneva as in Lake Ontario (Nalepa, 1991).…”
Section: Recovery Indicated By Worms 147mentioning
confidence: 74%
“…Furthermore, changes recorded in oUgochaete communities between 1982 and 1991 were the same as those attributed to a decrease of organic sedimentation (Lang, 1989b). However, the scardty of Peloscolex velutinus and Bythonomus lemani at a depth of 150 m (Lang, 1991), could indicate toxic effects in Lake Geneva as in Lake Ontario (Nalepa, 1991).…”
Section: Recovery Indicated By Worms 147mentioning
confidence: 74%
“…(hereafter Diporeia). Nalepa (1991) calculated that Diporeia was the dominant benthic invertebrate in profundal habitats of the Lakes Superior, Michigan, and Ontario, accounting for 69-91% of total benthic biomass. In recent years, however, Diporeia biomass has declined (by 90% in some areas) in Lake Michigan (Nalepa et al, , 2009, and similar population declines have been observed in Lakes Ontario (Dermott and Kerec, 1997;Lozano et al, 2003), Erie (Dermott, 2001), and Huron (Nalepa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sub-lethal effects of elevated sediment potentially include reduced immunity to disease, depressed growth rates, and impaired feeding and reproduction [22,23,[25][26][27][28][29][30][31][32][33].…”
Section: Sedimentmentioning
confidence: 99%